Prevalence of Aggression in Displaced Syrian Adolescents Attending Afternoon Public Schools in Beirut. (8th March 2019) - Bouclaous, Carmel; El Safadi, Ali; Basbous, Mazen; Haddad, Iskander; Mahdi, Ahmad; Zibara, Victor; Ghazi, Rabih; Naamani, Karim; El Karaaoui, Jalal; Salameh, Rim
Abstract: We assessed aggression in displaced Syrian adolescents, aged 11 years and above, enrolled in Beirut's public schools during 2017–2018. Of 729 parental consent forms distributed in nine randomly selected schools, 368 (50.5%) parents accepted to involve their children. Eventually, the revised Buss-Perry aggression questionnaire was used to assess physical aggression, verbal aggression, anger, and hostility in 178 boys and 182 girls. Scores were interpreted based on the adolescents' age, sex, year of arrival to Lebanon, and Syrian governorate from which they migrated last. Twenty four percent of participants scored high on aggression measurements. Boys had significantly higher scores than girls on verbal aggression ( p =0.001), hostility ( p =0.003) and total aggression ( p =0.007). When other variables were held constant, adolescents who fled to Lebanon in the early days of the Syrian war had significantly higher levels of verbal aggression ( p =0.044), hostility ( p =0.028) and total aggression ( p =0.007) than those who arrived later. Anger scores were not particularly affected by variables in our regression model. Adolescents from Idlib, Daraa, and Aleppo were predicted to have increased physical aggression scores. Verbal aggression scores were predicted to rise for adolescents from Daraa and Aleppo while other districts had a protective effect. These adolescents have witnessed the harshness and inhumanity of war, and have survived life-changing traumatic events. In view of our results, we recommend the introduction of a school-based universal cognitive behavioral intervention to reduce aggression in this vulnerable group both in Lebanon and upon their return to Syria.